Time-Frequency Based Channel Estimation for High-Mobility OFDM Systems—Part II: Cooperative Relaying Case. (7th June 2010) - Önen Önen, Erol Erol; Odabaşioğlu Odabaşioğlu, Niyazi Niyazi; Akan Akan, Aydın Aydın
Abstract : We consider the estimation of time-varying channels for Cooperative Orthogonal Frequency Division Multiplexing (CO-OFDM) systems. In the next generation mobile wireless communication systems, significant Doppler frequency shifts are expected the channel frequency response to vary in time. A time-invariant channel is assumed during the transmission of a symbol in the previous studies on CO-OFDM systems, which is not valid in high mobility cases. Estimation of channel parameters is required at the receiver to improve the performance of the system. We estimate the model parameters of the channel from a time-frequency representation of the received signal. We present two approaches for the CO-OFDM channel estimation problem where in the first approach, individual channels are estimated at the relay and destination whereas in the second one, the cascaded source-relay-destination channel is estimated at the destination. Simulation results show that the individual channel estimation approach has better performance in terms of MSE and BER; however it has higher computational cost compared to the cascaded approach.